Leadership Role Head Schools In Improving Teacher Performance - Hasni Julidawati; Lena Nofelia; Nurhizrah Gitituati (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The purpose of this study was to determine how the role of the principal's leadership in improving teacher performance at SMAN 1 Kampar Utara. This research uses qualitative research with descriptive research design. Data collection techniques were carried out by observation, interviews, and documentation. The results of this study indicate that there is a significant role between the principal's leadership in improving teacher performance at SMAN 1 Kampar Utara. There are 6 main roles of leadership in improving performance: 1) Applying a leadership style that is democratic, straightforward and open. 2) Provide time to communicate with teachers, students, and other school members. 3) Emphasize to teachers and all school members to comply with disciplinary norms. 4) Conduct regular and continuous meetings with teachers, school members, and school committees. 5) Guiding and directing teachers in solving problems. 6) Conduct class visits to observe directly learning activities.